Does Regulation Kill Jobs? - Carrigan, Christopher; Finkel, Adam M.; Coglianese, Cary (Book collections on Project MUSE., 2013)
As millions of Americans struggle to find work in the wake of the Great Recession, politicians from both parties look to regulation in search of an economic cure. Some claim that burdensome regulations undermine private sector competitiveness and job growth, while others argue that tough new regulations actually create jobs at the same time that they provide other benefits. Does Regulation Kill Jobs? reveals the complex reality of regulation that supports neither partisan view. Leading legal scholars, economists, political scientists, and policy analysts show that individual regulations can at times induce employment shifts across firms, sectors, and regions--but regulation overall is neither a prime job killer nor a key job creator. The challenge for policymakers is to look carefully at individual regulatory proposals to discern any job shifting they may cause and then to make regulatory decisions sensitive to anticipated employment effects. Drawing on their analyses, contributors recommend methods for obtaining better estimates of job impacts when evaluating regulatory costs and benefits. They also assess possible ways of reforming regulatory institutions and processes to take better account of employment effects in policy decision-making.Does Regulation Kills Jobs? tackles what has become a heated partisan issue with exactly the kind of careful analysis policymakers need in order to make better policy decisions, providing insights that will benefit both politicians and citizens who seek economic growth as well as the protection of public health and safety, financial security, environmental sustainability, and other civic goals.Contributors: Matthew D. Adler, Joseph E. Aldy, Christopher Carrigan, Cary Coglianese, E. Donald Elliott, Rolf Färe, Ann Ferris, Adam M. Finkel, Wayne B. Gray, Shawna Grosskopf, Michael A. Livermore, Brian F. Mannix, Jonathan S. Masur, Al McGartland, Richard Morgenstern, Carl A. Pasurka, Jr., William A. Pizer, Eric A. Posner, Lisa A. Robinson, Jason A. Schwartz, Ronald J. Shadbegian, Stuart Shapiro.